Does Financial Inclusion Increase MSME Financing at Islamic Banks During Covid 19? - Wibowo, Muhammad Yusuf Perkasa; Sriyana, Jaka (Journal of Finance and Islamic Banking, 2023)
The impact of Covid-19 on MSME has necessitated solutions through MSME financing at Sharia Banks, involving the role of financial inclusion to address their financial challenges. The purpose of this study is to analyze the role of financial inclusion in stimulating MSME financing during Covid 19 with a focus on the effect of financial inclusion on MSME financing at Islamic banks during covid 19. The method used is Panel Data Analysis with the best model chosen, namely the Fixed Effect Model with GLS weights used Seemingly Uncorrelated Regression to solve autocorrelation problems and a higher adjusted R-Square value. The object of research is Islamic Banks using secondary data from 33 provinces in Indonesia during the Covid-19 period, from March 2020 to December 2022 with total of 1122 observations. The results of this study imply that any increase in financial inclusion will increase Islamic Bank Financing for the MSME sector in each province in Indonesia. Furthermore, during this period, an increase in DPK can enhance the distribution of inclusive financing, while a rise in NPF ratio can reduce it. This research contributes by demonstrating that the increased inclusivity of financial services can enable easier and more affordable access to financial products and services offered by formal institutions, particularly in the context of financing for MSME, with the aim of improving overall well-being and addressing the impact of COVID-19.